Determinants of profitability of food industry in India - Azhakar, Ramachandran (Management, 2012)
Profitability is the profit earning capacity, which is a crucial factor in contributing to the survival of firms. This paper is a maiden attempt at estimating the impact of size on profitability, considering the Žsize' as the control variable. For this purpose, the selected firms are classified into three size categories as Žsmall,' Žmedium,' and Žlarge' based on the sales turnover. The results show that volatility and growth are the major predictorsin determining profitability in case of small size firms while growth is important in determining the profitability of medium size firms. Capital intensity has a significant positive coefficient with the profitability of large size firms. The overall result shows that the larger the size of the firm, the more the investment in long lived assets has helped to increase the profitability of the firm unlike the trend in cases of small size and medium size firms.
Keywords: dobiček; donosnost; India; Indija; investicije; podjetja; živilska industrija